2012
DOI: 10.1021/jp210008g
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Absorption Cross Sections of Formaldehyde in the 30285–32890 cm–1 (304–330 nm) Spectral Region

Abstract: Absolute room temperature (294 ± 2 K) absorption cross sections for the Ã(1)A(2)-X̃(1)A(1) electronic transition of formaldehyde have been measured over the spectral range 30,285-32,890 cm(-1) (304-330 nm) using ultraviolet (UV) laser absorption spectroscopy. Accurate high-resolution absorption cross sections are essential for atmospheric monitoring and understanding the photochemistry of this important atmospheric compound. Absorption cross sections were obtained at an instrumental resolution better than 0.09… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Comparison of the high-resolution absolute cross section, σ HCHO , obtained previously (top panel) with the action spectrum, relative Φ H+HCO σ HCHO , obtained at the same resolution (bottom panel).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Comparison of the high-resolution absolute cross section, σ HCHO , obtained previously (top panel) with the action spectrum, relative Φ H+HCO σ HCHO , obtained at the same resolution (bottom panel).…”
Section: Resultsmentioning
confidence: 97%
“…The composite action spectrum was placed on an absolute wavelength scale using the previously obtained wavelength calibrated high-resolution absorption cross section. The error in the wavelength calibration is ±0.096 cm –1 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rufus et al, 2003), formaldehyde (HCHO, e.g. Ernest et al, 2012) water (Rothman et al, 2013), and chlorine monoxide (ClO Barton et al, 1984), Neuroth et al (1991) found strong, discrete and narrow bromine monoxide (BrO) absorption lines in the UV. Using these much more detailed and specific spectral features of the trace gases could not only substantially increase the selectivity but also in many cases increase the sensitivity of DOAS measurements.…”
mentioning
confidence: 99%